Landscape character in landscape planning - Sallay, Ágnes (4D Journal of Landscape Architecture and Garden Art, 2015)
The Corvinus University of Budapest, Faculty of Landscape Architecture and the Hungarian Academy of Sciences traditionally organize an annual conference related to one of the actual topics of landscape architecture. This year's conference was held at the end of January under the title "The future of the landscape, the importance of landscape character in the landscape planning". Landscape character is what makes an area unique and different.
Keywords: landscape character; landscape planning